2013
DOI: 10.3758/s13415-013-0232-0
|View full text |Cite
|
Sign up to set email alerts
|

Detecting and correcting partial errors: Evidence for efficient control without conscious access

Abstract: Appropriate reactions to erroneous actions are essential to keeping behavior adaptive. Erring, however, is not an all-or-none process: electromyographic (EMG) recordings of the responding muscles have revealed that covert incorrect response activations (termed “partial errors”) occur on a proportion of overtly correct trials. The occurrence of such “partial errors” shows that incorrect response activations could be corrected online, before turning into overt errors. In the present study, we showed that, unlike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
41
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 46 publications
11
41
1
Order By: Relevance
“…The ANOVA revealed a main effect of trial type (F (1,11) ϭ 62.1, p Ͻ 0.001). Correct EMG bursts had a much higher amplitude compared with partial errors, consistent with previous work (Rochet et al, 2014;Burle et al, 2014). The interaction between trial type and congruency was also significant (F (1,11) ϭ 6.7, p Ͻ 0.05).…”
Section: Emg Datasupporting
confidence: 89%
See 1 more Smart Citation
“…The ANOVA revealed a main effect of trial type (F (1,11) ϭ 62.1, p Ͻ 0.001). Correct EMG bursts had a much higher amplitude compared with partial errors, consistent with previous work (Rochet et al, 2014;Burle et al, 2014). The interaction between trial type and congruency was also significant (F (1,11) ϭ 6.7, p Ͻ 0.05).…”
Section: Emg Datasupporting
confidence: 89%
“…Therefore, it is unclear whether it can explain the congruency effect on partial error EMG surfaces and the strong positive correlation between partial error rates and EMG MTs. In addition, it has been shown recently that partial errors are consciously detected in only 30% of cases (Rochet et al, 2014). It remains to be determined whether a commitment to a choice can occur without conscious access (see Shadlen and Kiani, 2013, for a discussion about the links between evidence accumulation and consciousness).…”
Section: Discussionmentioning
confidence: 99%
“…thoughts or emotions) and developing meta-awareness. Studies have revealed that only a third of partial errors 4 are consciously detected (Rochet, Spieser, Casini, Hasbroucq, & Burle, 2014). Our model suggests that mindfulness could improve the conscious perception of partial errors, and support their correction before they turn into overt errors.…”
Section: Enhanced Body Awareness In Mindfulnessmentioning
confidence: 57%
“…If the correct response is provided by the subject, this means that the partial error has been identified and corrected, preventing an overt error. Rochet et al studied whether partial errors are consciously detected by subjects (Rochet, Spieser, Casini, Hasbroucq, & Burle, 2014), and they showed that less than one-third of partial errors were reported. Even if partial errors are not consciously detected, however, they are being corrected for before producing an overt error.…”
Section: Consciousness Of Errors and Error Potentialsmentioning
confidence: 98%